Revamping India’s Workforce with the Skill India Mission: Bridging the Gap: Analyzing the Skill India Mission for Enhancing India's Workforce (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Skills and knowledge drive economic growth and social development of a country. Nations with higher levels and better standards of skilled workforce can deal with challenges and opportunities in the domestic and global market. India is one of the fastest-growing economies in the world and with one of the youngest work force, it has a huge potential demographic dividend. However, the quality of work force is not consistent with industry requirements so that are number of unfilled job requirements and simultaneous unemployment. In order to bridge this gap, there is a need to skill the people to increase their productivity and employability. The Skill India Mission, launched in 2015, aims to provide vocational training to the youth with emphasis on certification to increase their overall employability and earnings. This paper discusses the main features of the mission and examines its functioning, a year into its roll out, using published reports from government agencies, media and newspapers. It analyses the need for such programmes to accentuate the demographic dividend India currently has.